A method for rearing and assessing the health of the sugarcane pest Dermolepida albohirtum (Coleoptera: Scarabaeidae). (18th September 2022) - Lenancker, Pauline; Powell, Kevin S.
Abstract: Rearing insects in controlled conditions is a prerequisite to supply high‐quality specimens for bioassays. However, while artificial diets and standardized rearing methods have been developed for many phytophagous insects, especially Lepidoptera, there are limited published diets for root‐feeding Coleoptera which are commonly fed either grass roots or pieces of vegetables as a simple alternative to artificial diets during bioassays. These feeding options, while convenient, can be considered suboptimal as they do not maximise the insects' development and health. Additionally, it is also important to develop standardised screening methods designed to test sublethal effects of control agents which may have repellent, antifeedant, antimetabolic and/or delayed mortality effects. The greyback canegrub ( Dermolepida albohirtum, Waterhouse) is the most damaging native pest of Australian sugarcane, but no rearing method or artificial diet has ever been developed for this species. Our objectives were to improve bioassay methodology for D. albohirtum by describing and developing standard rearing and health assessment protocols. We describe a successful rearing method to raise healthy D. albohirtum larvae with a total of 48.8% of first instars successfully moulting to the second instar. We also tested a modified artificial diet which increased the weight, size and food uptake of larvae compared to traditional methods (i.e., pieces of carrots). For example, the average weight increase of larvae fed with the modified diet was 3.4 times higher than for carrot‐fed larvae while modified diet‐fed larvae were 2.1 times wider than if they were fed with carrots. Finally, we developed a method to measure larval activity which can be used to identify sublethal effects of control agents such as effects on activity level. Our methods may also be applied to improve bioassay methodology for other root‐feeding Coleoptera.